Evaluation of a brief anti-stigma campaign in Cambridge: do short-term campaigns work? - Evans-Lacko, Sara (BioMed Central, 2010)
BACKGROUND: In view of the high costs of mass-media campaigns, it is important to understand whether it is possible for a media campaign to have significant population effects over a short period of time. This paper explores this question specifically in reference to stigma and discrimination against people with mental health problems using the Time to Change Cambridge anti-stigma campaign as an example. METHODS: 410 face-to-face interviews were performed pre, during and post campaign activity to assess campaign awareness and mental health-related knowledge, attitudes and behaviours. RESULTS: Although campaign awareness was not sustained following campaign activity, significant and sustained shifts occurred for mental health-related knowledge items. Specifically, there was a 24% (p < 0.001) increase in persons agreeing with the statement: If a friend had a mental health problem, I know what advice to give them to get professional help, following the campaign. Additionally, for the statement: Medication can be an effective treatment for people with mental health problems, there was a 10% rise (p = 0.05) in the proportion of interviewees responding 'agree' or 'strongly agree' following the campaign. These changes, however, were not evident for attitudinal or behaviour related questions. CONCLUSIONS: Although these results only reflect the impact of one small scale campaign, these preliminary findings suggest several considerations for mass-media campaign development and evaluation strategies such as: (1) Aiming to influence outcomes pertaining to knowledge in the short term; (2) Planning realistic and targeted outcomes over the short, medium and long term during sustained campaigns; and (3) Monitoring indirect campaign effects such as social discourse or other social networking/contact in the evaluation.